Analisis Kelayakan Finansial Usaha Pengolahan Jagung Pada Rumah Tangga Tani di Desa Mantobua Kecamatan Lohia Kabupaten Muna - Salni, Dempu; Abdi, Abdi; Yusran, Yusran (Department of Agribusiness, Halu Oleo University, 2019)
This study aims to first determine the business income of maize processing in farm households in Mantobua Village, Lohia District, Muna Regency, secondly to find out the financial feasibility of a corn processing business in Mantobua Village, Lohia District, Muna Regency. The analysis used in this study is income analysis and financial feasibility analysis consisting of Net Present Value (NPV), Net Benefit Cost Ratio (NBCR), Internal Rate of Return (IRR), Payback period (PBP), Break Even Point (BEP ) and Sensitivity Analysis. The results of this study indicate that the processing of maize in Mantobua Village is still simple even though the processing has used a grater machine, and the grinder. Whereas in terms of business feasibility, corn processing business in Mantobua Village is feasible to be cultivated. Because at the 7% discount factor (df), the NPV value ofÂ Rp 10,131,577.4, NBCR of 38.85, IRR ofÂ 78.17%, PBP of 0.93 Years or 11 months of 16 days with a business life of 5 years, and BEP of production of 3,544 Kg and BEP of Rp 8419 / Kg. While the analysis of sensitivity feasibility where the condition of increasing production costs is 4.29% at a discount factor (df) of 7%, an NPV value of Rp 8,905,501, NBCR of 10.56, IRR of 81.9%, PBP of 0.99 years or 1 year. While the condition if the selling price decreases 4.29% is obtained NPV of Rp 8,272,844, NBCR of 8.09, IRR of 79.98% and PBP of 1.04 years or 12 months of 14 days. In these circumstances corn processing business in Mantobua Village is still feasible.